Alteration of Exon Definition Causes Amelogenesis Imperfecta. (April 2020) - Kim, Y.J.; Kang, J.; Seymen, F.; Koruyucu, M.; Zhang, H.; Kasimoglu, Y.; Bayram, M.; Tuna-Ince, E.B.; Bayrak, S.; Tuloglu, N.; Hu, J.C.-C.; Simmer, J.P.; et al.
Amelogenesis imperfecta (AI) is a collection of genetic disorders affecting the quality and/or quantity of tooth enamel. More than 20 genes are, so far, known to be responsible for this condition. In this study, we recruited 3 Turkish families with hypomaturation AI. Whole-exome sequence analyses identified disease-causing mutations in each proband, and these mutations cosegregated with the AI phenotype in all recruited members of each family. The AI-causing mutations in family 1 were a novel AMELX mutation [NM_182680.1:c.143T>C, p.(Leu48Ser)] in the proband and a novel homozygous MMP20 mutation [NM_004771.3:c.616G>A, p.(Asp206Asn)] in the mother of the proband. Previously reported compound heterozygous MMP20 mutations [NM_004771.3:c.103A>C, p.(Arg35=) and c.389C>T, p.(Thr130Ile)] caused the AI in family 2 and family 3. Minigene splicing analyses revealed that the AMELX missense mutation increased exonic definition of exon 4 and the MMP20 synonymous mutation decreased exonic definition of exon 1. These mutations would trigger an alteration of exon usage during RNA splicing, causing the enamel malformations. These results broaden our understanding of molecular genetic pathology of tooth enamel formation.